Geographical variations in king cobra (Ophiophagus hannah) venom from Thailand, Malaysia, Indonesia and China: On venom lethality, antivenom immunoreactivity and in vivo neutralization - Tan, Kae Yi; Ng, Tzu Shan; Bourges, Aymeric; Ismail, Ahmad Khaldun; Maharani, Tri; Khomvilai, Sumana; Sitprija, Visith; Tan, Nget Hong; Tan, Choo Hock (Elsevier, 2020)
The wide distribution of king cobra (Ophiophagus hannah), a medically important venomous snake in Asia could be associated with geographical variation in the toxicity and antigenicity of the venom. This study investigated the lethality of king cobra venoms (KCV) from four geographical locales (Malaysia, Thailand, Indonesia, China), and the immunological binding as well as in vivo neutralization activities of three antivenom products (Thai Ophiophagus hannah monovalent antivenom, OHMAV; Indonesian Serum Anti Bisa Ular, SABU; Chinese Naja atra monovalent antivenom, NAMAV) toward the venoms. The Indonesian and Chinese KCV were more lethal (median lethal dose, LD50 ~0.5 μg/g) than those from Malaysia and Thailand (LD50 ~1.0 μg/g). The antivenoms, composed of F(ab)’2, were variably immunoreactive toward the KCV from all locales, with OHMAV exhibited the highest immunological binding activity. In mice, OHMAV neutralized the neurotoxic lethality of Thai KCV most effectively (normalized potency = 118 mg venom neutralized per g antivenom) followed by Malaysian, Indonesian and Chinese KCV. In comparison, the hetero-specific SABU was remarkably less potent by at least 6 to10 folds, whereas NAMAV appeared to be non-effective. The finding supports that a specific king cobra antivenom is needed for the effective treatment of king cobra envenomation in each region. © 2019 Elsevier B.V.